PENGARUH QUALITY OF WORK LIFE DAN SELF DETERMINATION TERHADAP WORK ENGAGEMENT PEGAWAI DINAS LINGKUNGAN HIDUP KABUPATEN ROKAN HULU - Rhoma Dani (Fakultas Ekonomi Universitas Pasir Pengaraian, 2021)
This study aims to analyze the effect of quality of work life and self- determination affect the work engagement of Rokan Hulu Regency Environmental Services Officers. Thepopulation of this study were all employees of the Rokan Hulu District EnvironmentalAgency. The sampling method uses saturated sampling (census). The analysis techniqueused is multiple linear regression analysis using the SPSS 18 program. The results of thestudy based on multiple linear regression analysis show that quality of work life and selfdetermination have a positive and significant effect on the work engagement of Rokan HuluRegency Environmental Service Officers. The conclusion of this study is based on partialtesting only the quality of work life variable that has a positive and significant effect on thework engagement of Rokan Hulu Regency Environmental Services Officers while on thesimultaneous testing all variables namely quality of work life and self determination affectwork engagement Rokan Hulu Regency Environmental Services Officer.